Brief Eclectic Psychotherapy for an Older Dutch Woman With Late-Onset Posttraumatic Stress Disorder Complicated by a Cerebral Vascular Accident. (October 2014) - Gielkens, Ellen M. J.; van Alphen, Bas; Sobczak, Sjacko; Segal, Daniel L.
Posttraumatic stress disorder (PTSD) is a mental disorder that is known to have deleterious psychological, physical, and social impacts on individuals. Recognition of PTSD in older adults is difficult due to the complicated presentation taking into account that PTSD symptoms may be masked by other psychiatric and/or somatic diagnoses that are more common in older adults. Furthermore, some older adults may underreport their PTSD symptoms, and the relationship between current symptoms and distant traumas may be difficult to detect. Limited empirical research has been done on the manifestation, course, and treatment of PTSD in older adults. In this article, the literature on PTSD in older adults is reviewed, including discussion of common diagnostic problems, illustrated by a case report of an older woman with late-onset PTSD after a cerebral vascular accident (CVA). In conclusion, identifying PTSD in older adults can be difficult. However, detecting PTSD in older adults is critically important so that possibly hidden or masked trauma symptoms can be addressed in treatment, even if there are complicating factors such as a CVA.